2016
DOI: 10.1016/j.ijheh.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and blood cadmium and lead and kidney function: NHANES 2007–2012

Abstract: Background Cadmium (Cd) and lead (Pb) are widespread environmental contaminants that are known nephrotoxins. However, their nephrotoxic effects at low-environmental exposure levels are debated. Objective We examined the association of blood Pb (B-Pb), blood Cd (B-Cd), urinary Pb (U-Pb) and urinary Cd (U-Cd) with estimated glomerular filtration rate (eGFR) and urinary albumin (ALB). Methods We used multivariate linear regression to analyze the association between B-Pb, B-Cd, U-Pb, and U-Cd with eGFR and ALB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(83 citation statements)
references
References 37 publications
8
73
1
1
Order By: Relevance
“…The authors suggested that urinary cadmium is a more appropriate biomarker if chronic diseases with long latency are examined. Several previous studies have also reported inconsistent associations between blood cadmium and urinary cadmium (Ali et al, 2014; Buser et al, 2016). Given that cataract is a chronic disease with long latency, weaker associations found with blood cadmium in our study may be due to non-differential measurement error which may lead the observed associations toward the null (Tellez-Plaza et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…The authors suggested that urinary cadmium is a more appropriate biomarker if chronic diseases with long latency are examined. Several previous studies have also reported inconsistent associations between blood cadmium and urinary cadmium (Ali et al, 2014; Buser et al, 2016). Given that cataract is a chronic disease with long latency, weaker associations found with blood cadmium in our study may be due to non-differential measurement error which may lead the observed associations toward the null (Tellez-Plaza et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Urinary Cd levels among the NHANES 1999-2008 participants, 20-85 yrs of age, indicated overall Cd exposure prevalence of 94-98% in non-smokers and 96-99% in smokers (Riederer et al 2013). Overall Cd exposure prevalence among NHANES 2007-2012 participants, aged ≥ 20 yrs, was 91.9% (Buser et al 2016). Fig.…”
Section: Urinary Cadmium Levels As a Measure Of Long-term Exposurementioning
confidence: 90%
“…Since most lead is initially stored largely in the kidneys and liver, it can cause pathobiological changes in these organs. Chronic lead poisoning can result in chronic kidney disease and a reduction in the number and volume of renal glomeruli . Lead also causes oxidative cellular and tissue damage to the liver .…”
Section: Introductionmentioning
confidence: 99%